2022
DOI: 10.5817/csf2022-2-76
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin at sub-cardiotonic dose modulates the anticonvulsive potential of valproate, levetiracetam and topiramate in experimental primary generalized seizures

Abstract: The prevalence of epilepsy in the world population together with a high percentage of patients resistant to existing antiepileptic drugs (AEDs) stimulates the constant search for new approaches to the treatment of the disease. Previously a significant anticonvulsant potential of cardiac glycoside digoxin has been verified by enhancing a weak activity of AEDs in low doses under screening models of seizures induced by pentylenetetrazole and maximal electroshock. The aim of the present study is to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In previous studies, we found the presence of a pronounced anticonvulsant effect of digoxin per se, as well as its potentiating effect on classical commonly used antiepileptic drugs (AEDs) in acute primarly generalized models of seizure, induced by pentylenetetrazole (PTZ), picrotoxin, thiosemicarbazide, strychnine, camphor and maximal electroshock in mice (Tsyvunin et al 2020(Tsyvunin et al -2022.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found the presence of a pronounced anticonvulsant effect of digoxin per se, as well as its potentiating effect on classical commonly used antiepileptic drugs (AEDs) in acute primarly generalized models of seizure, induced by pentylenetetrazole (PTZ), picrotoxin, thiosemicarbazide, strychnine, camphor and maximal electroshock in mice (Tsyvunin et al 2020(Tsyvunin et al -2022.…”
Section: Introductionmentioning
confidence: 99%
“…The use of non-antiepileptic medicines as adjuvant agents, which have anticonvulsant properties and enhance the effects of classical AEDs, is gaining more comprehensive application. Such medicines include, in particular, non-steroidal anti-inflammatory medicines, sodium channel blockers (in particular, lidocaine), slow calcium channel blockers, β-blockers, the If-channel blocker ivabradine, the competitive xanthine oxidase inhibitor allopurinol, statins, selective phosphodiesterase-5 inhibitors (sildenafil, tadalafil), the cardiac glycoside digoxin [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%